Overexpression of Tobacco GCN2 Stimulates Multiple Physiological Changes Associated With Stress Tolerance - Li, Ning; Zhang, Song-jie; Zhao, Qi; Long, Yue; Guo, Hao; Jia, Hong-fang; Yang, Yong-xia; Zhang, Hong-ying; Ye, Xie-feng; Zhang, Song-tao (Frontiers in Plant Science, 2018)
General control non-derepressible-2 (GCN2) is a ubiquitous protein kinase that phosphorylates the α subunit of eukaryotic initiation factor eIF2, preventing the recycle of protein synthesis initiation, subsequently reducing the global protein biosynthesis. GCN2 could act as a regulator to response to biotic and abiotic stresses. In this study, two homologues, NtGCN2-1 and NtGCN2-2 were cloned from Nicotiana tabacum, which were shown to be derived from its progenitors N. tomentosiformis and N. sylvestris, respectively. The phosphorylation of NteIF2α could be activated by promoting the expression of NtGCN2 with plant hormones including salicylic acid (SA), azelaic acid (AZA), methyl jasmonate (MeJA), and different stresses (Bemisia tabaci infection, drought and cold), indicating that NtGCN2 is involved in responding to multiple biotic and abiotic stresses. The results showed that overexpression of NtGCN2-1 significantly influenced different physiological processes. Overexpression of GCN2 promoted seed germination and root elongation. Contents of total soluble sugars and reducing sugars were decreased, while contents of chlorophyll a and b were increased in the overexpressed plants. In addition, lower reactive oxygen species (ROS) and higher antioxidant activities were displayed in overexpressed plants. These physiological alterations could be attributed to the changes of endogenous phytohormones, decreases of SA and abscisic acid (ABA) and accumulation of MeJA and AZA. It indicated that overexpression of NtGCN2 in tobacco stimulated plant defense responses via phosphorylation of NteIF2α and regulation of plant hormones, changes of antioxidant ability, as well as shifts of plant nutrient status.